690 National survey of injury prevention activities of children's centres. (1st September 2016) - Watson, Michael Craig; Mulvaney, Caroline; Timblin, Clare; Stewart, Jane; Coupland, Carol; Deave, Toity; Hayes, Mike; Kendrick, Denise
Abstract : Background: Children's centres were established across England to improve health outcomes for children. Injury prevention is one of the many roles centres have in protecting and promoting children's health. The centres have the potential to make significant contributions to home safety for children under five. The aim of this study was to ascertain the activities undertaken by children's centres to prevent unintentional injuries in the under fives and in particular, the prevention of falls, poisoning and scalds. Methods: A questionnaire was posted to managers of 851 children's centres, selected by stratified cluster sampling. The questionnaire included questions on injury prevention activities undertaken by the centre, knowledge and attitudes to injury prevention, partnership working, and barriers and facilitators to injury prevention. Results: A response rate of 61% was achieved. Most respondents (98%) agreed that children's centres can be effective in preventing accidents. Over half the respondents (59%) did not know if there was an injury prevention group in their area, and 22% did not know if there was a home safety equipment scheme. Only 12% knew the major cause of injury deaths in children under five. A variety of activities were being undertaken including one to one advice and issuing leaflets. However, for some important topics such as baby walkers, and disposal of unwanted medicines no advice was being provided in some areas. Lack of funding (52%) and lack of capacity (39%) were the most common reasons cited as barriers to injury prevention activities. Conclusions: Injury prevention is an important activity undertaken by children's centres. Given their position in the heart of the community their potential as an agency to prevent injuries has been highlighted and recommended. Further support and resource will be needed if they are to fully develop their potential in preventing unintentional injuries in the home.